The Customer Purchasing Situation Outcomes of Celebrity Endorsement and Brand Awareness Activities: English - Firdhaus, Faidzin; Ikhtiagung, Ganjar Ndaru; Sarapil, Costantein Imanuel; Vionika, Igna Findy (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The aim of this study was to investigate the role of celebrity endorsement and brand awareness activities on the consumer purchasing situation of halal cosmetic products, especially Wardah brand products. The sample in this study consisted of 384 respondents in Central Java, Indonesia, where the characteristics of the respondent are female or female and consist of several types of nominal data such as age, occupation, income, and education. This survey was conducted on female respondents aged 18–40 years and of course, have purchased or have never purchased Wardah whitening cream products. This study shows that there is a positive influence between celebrity endorsements and brand awareness. Another important finding in the research is that the celebrity endorsement variable has a significant and significant effect on the purchase intentions variable. This study clearly finds that the brand awareness variable has no effect on the purchase intention variable. There is no influence of brand awareness variables on purchase intentions in this research because brand awareness is in the range between feelings of uncertainty about brand recognition. In addition, in the findings of this study, it is known that the brand awareness variable has no role in mediating the relationship between celebrity endorsement variables and purchase intentions.